Potassium Persulfate-Promoted N-Nitrosation of Secondary and Tertiary Amines with Nitromethane under Mild Conditions - Azeez S.; Chaudhary P.; Sureshbabu P.; Sabiah S.; Kandasamy J. (My University, 2025)
A simple and efficient route for the N-nitrosation of various secondary amines with nitromethane is described in the presence of potassium persulfate and DBU. Under optimized condition, tertiary amines underwent a dealkylative N-nitrosation with good yields. Inexpensive reagents, broad substrate scope and efficient conversion make the current protocol more attractive in organic synthesis. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim